Controlling Indomethacin Release through Vapor-Phase Deposited Hydrogel Films by Adjusting the Cross-linker Density - Paul Christian (Nature Portfolio, 2018)
Abstract Vapor-phase deposited polymer coatings are applied on thin indomethacin films to modify the drug release. Hydrogel-forming co-polymers of 2-hydroxyethyl methacrylate and ethylene glycol dimethacrylate were prepared directly on top of solution cast indomethacin thin films by initiated Chemical Vapor Deposition (iCVD). This technique allows for solvent-free processing under mild conditions, thus minimizing a potential impact on the pharmaceutical. The drug release behavior, among other properties, was evaluated for polymers of different compositions and at different temperatures. The data show that the release kinetics can be tuned by several orders of magnitude as the cross-linker fraction is varied in the polymer coating. While uncoated indomethacin films were fully released within an hour, polymer coatings showed gradual liberation over several hours to days. Additional insight is gained from evaluating the experimental dissolution data in the framework of diffusive transport. The results of this study show that the iCVD technique has some promises for pharmaceutical technology, potentially allowing for tailored release behavior also for other drug systems.